Early Automated Detection of the Causes and Precursors of Human Stampedes in the Holy Sites and the Grand Mosque in Makkah (The International Journal for Scientific Research, 2026)
Within the framework of the continuous and concerted efforts undertaken by the Kingdom of Saudi Arabia to develop the Grand Mosque and the Holy Sites, the recent mega-expansion project represents the culmination of these endeavors. This expansion has significantly enhanced the urban and architectural quality of these sacred sites while substantially increasing their accommodation capacity. With the anticipated rise in the number of pilgrims and worshippers, particularly during peak periods such as the month of Ramadan and the Hajj season, there is a critical need to strengthen organization, coordination, monitoring, and crowd management mechanisms. This need is especially pronounced in highly congested areas, notably Mina during the stoning of the Jamarat, as well as the Tawaf and Sa’i areas of the Grand Mosque, where crowd density reaches its maximum and most stampede incidents tend to occur. This paper proposes an innovative design concept for an integrated electronic monitoring system aimed at the early automatic detection of the causes and precursors of crowd congestion and stampedes in sensitive areas of the Holy Sites, including the Jamarat Bridge, the routes leading to it from Muzdalifah, and the Tawaf and Sa’i areas within the Grand Mosque. The system is designed to effectively track the movement, direction, and speed of all individuals present in these areas without exception, and to automatically detect any violations of the regulations and guidelines stipulated in the official crowd management plans issued by the responsible authorities, whether such violations are individual or collective. The violations that the proposed system can automatically detect include exceeding permitted movement speed limits, such as rushing in designated waiting zones or slowing down in continuous-flow areas, violating prescribed movement directions by walking against the designated flow of pilgrims, adopting irregular or zigzag movement patterns, or moving laterally across crowd streams. The system is also capable of identifying crowd density levels that exceed predefined thresholds, instances of floor sitting or sleeping, fixed and mobile unauthorized vending, carrying luggage, presence in restricted areas, and irresponsible behaviors that could potentially lead to disorder or unrest among pilgrims. The proposed designs also ensure full integration of all system components, encompassing the preparation of the electronic database and its contents, configuration procedures for all system devices, detailed explanations of optical sensor operation, automated image processing and matching techniques for violation detection, and clarification of the roles of control, decision-making, intervention, alert, and warning units. The designs demonstrate the system’s capability to automatically detect violations and forward them to a final evaluation stage for appropriate decision-making and corrective action. In emergency situations, the system can partially or fully halt or slow down crowd movement across the Holy Sites, direct intervention teams to incident locations, guide them to the nearest exits, and identify the safest routes for medical assistance, evacuation, and incident mitigation. Furthermore, the designs highlight the system’s scalability and capacity for continuous development. The study also addresses communication methods and interconnections between system units, the software solutions required to perform the system’s tasks, and presents examples of devices suitable for deployment across the various system components. Finally, the paper provides a set of recommendations intended to assist in establishing the initial steps necessary for implementing the proposed concept in practice.
Keywords: Early Detection; Human Stampede; Hajj; Holy Sites; Makkah; Jamarat Bridge; Automated System